Musyarakah Mutanaqisah: Strengthening Islamic Financing in Indonesia and Addressing Murabahah Vulnerabilities - Asyiqin, Istianah Zainal; Alfurqon, Fe Fikran (Jurnal Media Hukum, 2000)
The article analyses to examine the practice of murabahah and musyarakah mutanaqisah financing in sharia banking in Indonesia. Islamic finance plays an important role in the Indonesian economy, contributing to financial inclusion and encouraging ethical practices and sharia compliance. Among the various Islamic financing models, musyarakah mutanaqisah has become famous as an alternative to conventional financing methods. The aticle method used is qualitative research with secondary data and doctrinal legal study methods. This article uses sustainable product innovation, modernization, and compliance with sharia principles. The results of the article found that the implementation of murabahah has several weaknesses, including: it is considered not in accordance with sharia, the nature of the contract is fixed, the down payment for sharia housing loans by murabahah is high, it is based on sharia, and cannot be used for refinancing, takeovers, and securing assets. The advantages of musyarakah mutanaqisah can be a solution to murabahah's weaknesses, because musyarakah mutanaqisah is safe according to sharia, suitable for long-term financing, down payments for sharia mortgages by musyarakah mutanaqisah are low, and according to sharia, musyarakah mutanaqisah can also be used for refinancing, takeovers and securing assets.